2015
DOI: 10.1186/s13075-015-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of rheumatoid arthritis: a systematic review and dose-response meta-analysis

Abstract: IntroductionThe evidence from published studies on the association between obesity and rheumatoid arthritis has been contradictory. To clarify the association between obesity and rheumatoid arthritis, we conducted a systematic review and dose-response meta-analysis to assess the relationship between body mass index and rheumatoid arthritis risk.MethodsA systematic literature search of PubMed and Embase (up to 12 July 2014) was performed to identify all eligible published reports. The pooled relative risk resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
154
0
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 41 publications
8
154
0
7
Order By: Relevance
“…Among these large studies, obesity was not consistently associated with a significantly increased risk of incident RA in the population overall, and when present, the association was relatively modest, with HR ranging between 1.0 and 1.49 (Table 1) [12•, 19••, 20••, 21, 22•]. A recent meta-analysis of 11 studies, including 5 recent studies, did find a significant association between obesity and RA with a relative risk 1.31 (95 % CI 1.12 to 1.53), although because there was significant heterogeneity between studies, calculating a pooled relative risk is potentially problematic [23]. …”
Section: Obesity and The Risk Of Developing Ramentioning
confidence: 99%
“…Among these large studies, obesity was not consistently associated with a significantly increased risk of incident RA in the population overall, and when present, the association was relatively modest, with HR ranging between 1.0 and 1.49 (Table 1) [12•, 19••, 20••, 21, 22•]. A recent meta-analysis of 11 studies, including 5 recent studies, did find a significant association between obesity and RA with a relative risk 1.31 (95 % CI 1.12 to 1.53), although because there was significant heterogeneity between studies, calculating a pooled relative risk is potentially problematic [23]. …”
Section: Obesity and The Risk Of Developing Ramentioning
confidence: 99%
“…Obesity increases the risk of developing chronic diseases such as hypertension, diabetes mellitus, coronary heart disease, and rheumatoid arthritis (RA) (3, 4). …”
Section: Introductionmentioning
confidence: 99%
“…Another two studies reported no statistically significant associations between BMI or BMI categories and RA [13, 14]. The comparison between studies is hampered by differences in methodology, but a recent meta-analysis suggested a 30% increase in the risk of RA overall in obesity compared with normal weight [17]. …”
Section: Introductionmentioning
confidence: 99%